Overview of Compliance with the Use of Oral Antidiabetic Drugs in Diabetes Mellitus Patients - Ramadhini, Dhita; Lanaya, Dela; Sari, Lana; Zahriah, Zahriah (Journal of Health Sciences and Epidemiology, 2024)
Diabetes mellitus is a chronic disease caused by metabolic disorders of the pancreas and is characterized by an increase in blood sugar>126 mg/dl. In 2023, the number of diabetes mellitus patients redeemed for drug prescriptions at the Pangkalbalam Health Center was 1,697 people. The study aimed to measure compliance with oral antidiabetic drugs in patients with diabetes mellitus at the Pangkalbalam Health Center in Pangkalpinang City in 2024. The method used was descriptive, observational, and quantitative, with a cross-sectional approach. This study used accidental sampling, with a total sample of 96 respondents. The research instrument was a questionnaire, and data were analyzed using the univariate method. The measurement tool was a questionnaire administered to patients with diabetes mellitus at the Pangkalbalam Health Center and analyzed using the univariate method. The compliance level with oral antidiabetic drugs at the Pangkalbalam Health Center, Pangkalpinang City, in 2024 was 59,4%, categorized as moderate compliance. The Community Health Center needs to provide a unique monitoring form for compliance with diabetes mellitus patients.